DETERMINATION OF THE TRAINING NEEDS BY USING BORICH MODIFIED EQUATION FOR AGRICULTURAL EXTENSION WORKERS IN SOME GOVERNORATES OF NORTHERN IRAQ IN THE FIELD OF PLANNING AGRICULTURAL EXTENSION PROGRAMS - Aamil F. Al-Abbassi (Mesopotamia Journal of Agriculture)
The objective of this research is to assess the inservice training needs of the agricultural extension workers in Duhok & Erbil Governorates in the field of planning extension programmes and to find out if significant differences exist in the training needs according to some factors. The research sample included (71) respondents, the data were collected through a questionnaire which was specially designed for assessing the training needs by Borich model after testing the validity and reliability of the questionnaire. The researcher used analysis of variance, t-test, and rank–order correlation to analyze the data. A need for training the extension workers was found in the field of planning extension programs and this need was greater for the workers in Duhok Governorate and priorites of the need differ between the two Govermorates, It was also found that there was no significant differences in the training needs according to, age, race, gender, academic level, specialization, position in extension, place of work, years of employment, years of extension employment, and previous training.